Kapitalisasi Tubuh Perempuan dalam Iklan Televisi - Muhammad Imam Zamroni (Program Studi Ilmu Komunikasi, 2007)
Woman body in the television advertisement becomes instrument to accumulate the capital. This article aims to describe role of television advertisement to communicate each other, give information, define new product, accumulate the capital and increase consumptive culture by using woman body which have magnetic power. Gender inequality and objectification are always presented in the advertisement design, become one of woman exploitation manifestation. Advertisement establishes dominant culture which present man as leader, powerful, strong and heroic. Whereas, woman describes in the physical beauty, emotional and weak. Woman body is represented by television advertisement to promote every products and get large advantage rapidly.